Towards Developing Quantitative Structure-activity Relationship Models for the Design of Novel Influenza A Inhibitors Targeting Neuraminidase - Thanh, Ly Cong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1DO - 10.25073/2588-1132/vnumps.4412, 2023)
Abstract: Anti-influenza-A drugs targeting viral neuraminidase have been in use for two decades. In this study, the quantitative structure-activity relationships (QSAR) of oseltamivir derivatives as influenza neuraminidase (IN) inhibitors have been explored using the Monte Carlo method based on the target function involving the index of the ideality of correlation. Three best-obtained models showed appropriate performance with R 2 values of training and test sets ranging from 0.71 to 0.86, respectively. Based on the structural information extracted from the models, new inhibitors were designed and predicted for IN activities. Finally, protein docking was applied to confirm their target binding ability. Keyword : Anti-influenza A; neuramidase inhibitor; drug design; QSAR; docking.